Other-regarding preferences, spousal disability and happiness evidence from German couples - Nils Braakmann (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2009)
This paper considers the impact of adverse health shocks that hit an individual's partner on subjective well-being. Using data on couples from the German Socio-Economic Panel for the years 1984 to 2006, I compare the losses in well-being caused by own and spousal disability using panel-regressions. I find that women and to a lesser extent men are harmed by spousal disability which is consistent with the existence of other-regarding preferences within couples. The magnitude of effects suggests that spousal disability is about one quarter to one half as harmful as individual disability with larger effects being found for women.
Keywords: D64; I10; J14; 330; Disability; subjective well-being; other-regarding preferences